Virtual and augmented reality for anxiety reduction in orthopedic patients and providers: a systematic review - Negarsadat Namazi; Yashar Khani; Amirhossein Salmannezhad; Mohammad Behdadfard; Ehsan Safaee; Mohammad Nouroozi; Amir Mehrvar (Journal of Orthopaedic Surgery and Research)
Abstract Background Anxiety impacts patients and healthcare providers during orthopedic procedures, yet virtual reality (VR) and augmented reality (AR) effectiveness remains inconsistently reported, lacking systematic synthesis in this setting. This review addresses this gap. Methods Per PRISMA guidelines (PROSPERO: CRD42024553394), we searched PubMed, Scopus, Web of Science, and Embase in March 2024 for studies on VR/AR/mixed reality (MR) interventions for anxiety in orthopedic procedures. Data were narratively synthesized; bias assessed via RoB-2 and ROBINS-I. Results Twenty-four studies (16 RCTs, 8 cohort, n = 1714) showed VR (22 studies) and AR (2 studies) significantly reduced anxiety across procedure phases, notably in pediatrics. Healthcare providers (HCPs) reported lower anxiety and higher confidence with VR. Satisfaction rose, anesthetic use dropped, though inconsistent tools and methods limited comparisons. Conclusion VR/AR reduce pediatric anxiety in orthopedics, with less conclusive adult/HCP benefits. Clinicians could adopt preoperative VR. Research needs standardized tools and adult-focused RCTs.